Gestational and Age-Specific Cystatin C Reference Intervals for Newborns - Tong, Chao; Liu, Yalan; Wu, Yanqiu; Li, Qiong; Wu, Yipin; Wang, Lin; Chen, Yan (American Journal of Perinatology, 2021)
Objective Cystatin C (CysC) references are useful for the monitoring of renal function in neonates. However, the standard CysC references in newborn infants have not been determined. The aim of this study was to establish a useful reference range for CysC in newborns.Study Design Serum CysC levels were measured in 1,919 blood samples from 1,044 newborns during their first 28 days of life. CysC levels were analyzed for associations between subgroups dichotomized by postnatal age (PA) and gestational age (GA). The serum CysC reference intervals were determined according to the PA and GA. The associations between the serum CysC level and other biochemical parameters as well as perinatal factors were also analyzed.Results In this study, the mean GA was 35.8 ± 2.9 weeks and the birth weight (BW) was 2,614 ± 697 g. Reference ranges of serum CysC were determined, and a general decreasing trend of CysC levels was observed as the GA increased. CysC levels differed significantly among the PA and GA categories (p < 0.001). Serum CysC levels were relatively stable throughout the GA range but were impacted by the white blood cell count within the first postnatal 24 hours. Moreover, CysC levels always correlated positively with serum creatinine concentrations (p < 0.001). Serum Cr levels were influenced by multiple factors, including BW, GA, total bilirubin, direct bilirubin, white blood cell count, C-reactive protein, and blood urea nitrogen.Conclusion Reference levels of serum CysC should be determined according to the PA and GA. In contrast to Cr, serum CysC is a reliable index for assessing renal function in neonates as it is influenced by very few factors. The CysC reference levels will allow neonatologists to accurately evaluate renal function in the neonatal population.Key Points
Keywords: cystatin C; newborn; reference; renal function; creatinine